Analisis Studi Hadis atas Tradisi Sedekah Berbagi Takjil Setiap Ramadan di Desa Dalu X B di Masjid As-Shiddiq Kecamatan Tanjung Morawa - Citra, Nurul (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The tradition of sharing takjil (the fasting meal) during Ramadan is a form of practicing Islamic values that has grown in the community, particularly in Dalu X B Village, Tanjung Morawa District. This practice takes place annually at the As-Shiddiq Mosque and has become a collective custom for residents in welcoming the holy month of Ramadan. This tradition not only has social value but also has strong roots in Islamic teachings, particularly in the hadiths of the Prophet which encourage people to share food, strengthen brotherhood, and achieve the blessings of Ramadan. This study aims to analyze the tradition of sharing takjil in this location using a hadith study approach, in order to examine how the values of the hadith are implemented in the community's social practices. The method used is a qualitative case study approach. Data were obtained through observation, interviews, documentation, and a review of relevant hadith literature. The results show that the tradition of sharing takjil is a concrete form of understanding and practicing hadith, such as the hadith that recommends feeding fasting people and the hadith about the importance of strengthening Islamic brotherhood. Furthermore, there are strong spiritual, social, and educational transformational dimensions within this practice, such as increased youth participation, solidarity among residents, and the active role of mosque administrators in cultivating good values. In conclusion, this tradition is an effective means of translating the teachings of the hadith into collective actions that foster blessings and strengthen the religious community.